2021
DOI: 10.1007/s00792-021-01221-4
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity present on rocks from a polar desert in continental Antarctica assessed using DNA metabarcoding

Abstract: We evaluated the fungal diversity associated with carbonate veins and two types of salt encrustation in rocks in a polar desert region of continental Antarctica using DNA a metabarcoding approach. We detected 262,268 reads grouped into 517 amplicon sequence variants (ASVs) assigned to the phyla Ascomycota, Basidiomycota, Mortierellomycota and Mucoromycota. Fourteen ASVs belonging to the genera Trichosporon, Mortierella, Penicillium, Aspergillus, Cladosporium, Coprinellus, Pleurotus and Pseudogymnoascus were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
4
12
1
Order By: Relevance
“…In addition, recognized plant and animal pathogens were detected with different abundances, including Aspergillus , Candida , Cryptococcus , Cutaneotrichosporon , Fusarium , Malassezia and Rhodotorula . The same functional ecological profile detected for fungi present in marine sediments here have also been reported in studies sampling fungi in soil 12 , air 31 , lake sediment 43 and rocks 49 in Antarctica. However, we recognize that, as this study detected environmental DNA, further functional ecological studies are required to better understand the role and importance of fungi in these Antarctic marine sediments.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, recognized plant and animal pathogens were detected with different abundances, including Aspergillus , Candida , Cryptococcus , Cutaneotrichosporon , Fusarium , Malassezia and Rhodotorula . The same functional ecological profile detected for fungi present in marine sediments here have also been reported in studies sampling fungi in soil 12 , air 31 , lake sediment 43 and rocks 49 in Antarctica. However, we recognize that, as this study detected environmental DNA, further functional ecological studies are required to better understand the role and importance of fungi in these Antarctic marine sediments.…”
Section: Discussionsupporting
confidence: 87%
“…Considering the unique habitat provided by arid areas, it seems that the typical harsh environmental conditions of extreme desert lands truly reduce the number of plant endophytes. However, compared to other studies in similar extreme environments [26,73,74], the diversity of these microbial communities in our study is still relatively high in this arid desert, which may be associated with microenvironmental heterogeneity that is characteristic of the arid environment. Massimo et al [9] also demonstrated that fungal endophytes in desert plants were highly diverse and distinctive symbionts but infrequent in culture.…”
Section: Fungal Community Associated With Xerophytic Desert Shrubscontrasting
confidence: 80%
“…Fungal Taxonomy, Fungal Diversity, and Fungal Lifestyle Existing studies of endolithic fungal communities present in Antarctic rocks have involved their direct observation in the substrate, cultivation techniques, or cultureindependent methods [13]. Rocks from Antarctic can be considered a unique microhabitat for life forms, providing a natural habitat for rock-inhabiting microbes, including fungal taxa [7,13,17]. In the extreme conditions across Antarctica, endolithic fungi present within rocks are dominated by the phyla Ascomycota and Basidiomycota, as revealed by studies using traditional culturing methods [13].…”
Section: Discussionmentioning
confidence: 99%